PERAN GENDER DALAM MEMODERASI PENGARUH PERCEIVED BENEFIT DAN PERCEIVED COST TERHADAP NIAT MENGGUNAKAN KARTU KREDIT DI KOTA DENPASAR - Intan Kirana, I Dewa Ayu; Kerti Yasa, Ni Nyoman (E-Jurnal Manajemen; Vol 2 No 11 (2013), 2013)
Every consumer of men or women have a different perspective that may affect the intention to use a credit card. One factor to consider is the perceived benefits and perceived cost. The purpose of this study was to determine the effect of perceived benefits and perceived cost to the intention to use a credit card as well as the role of gender in moderating influence of perceived benefits and perceived cost to the intention to use credit cards in the city of Denpasar. The research was conducted in the city of Denpasar. Number of samples taken as many as 100 people with non-probability sampling method especially purposive sampling. The data was collected through questionnaire . The analysis technique used is Moderated Regression Analysis. The results showed perceived benefits and significant positive effect on the intention to use a credit card, while the perceived cost and significant negative effect on the intention to use credit cards in the city of Denpasar. This shows that the higher the perceived benefits of the higher consumer intentions to use a credit card. Conversely, the higher the cost, the lower the perceived intentions of consumers to use credit cards. Gender as a moderating variable shown to moderate the effect of perceived benefit, but not proven to moderate the effect of perceived cost on the intention to use credit cards in the city of Denpasar. Keywords : gender, perceived benefits, perceived cost, the intention to use credit card